Green tea extract: A natural antimicrobial with great potential for controlling native microbiota, Listeria innocua and Escherichia coli in fresh-cut beet leaves - Fernandez, María Verónica (2018)
Antimicrobial effect of green tea (GTE), nisin (Ni), natamycin (Na), and their combinations on native mesophilic bacteria (MAB), Enterobacteriaceae (EB), and molds and yeast (M&Y) of fresh-cut beet leaves and on inoculated Listeria innocua (LI) and Escherichia coli (EC) were determined during storage at 15 °C. Individual treatments with Ni and Na were not effective in reducing nor controlling native microbiota. Conversely, treatments containing GTE 5% reduced MAB and EB initial counts to values below detection limit (DL = 1 log UFC/g) for 24 hr. The most effective treatment for M&Y was the combination of GTE with Na, which maintained the counts in undetectable values (